Development of the Mbojo Culinary Application in Local Content Learning to Improve Students' Knowledge of Bima Traditional Cuisine - Laudiya Centiya Della; Mariamah Mariamah; Hardiansyah Hardiansyah (Jurnal Inovasi Pendidikan dan Sains, 2025)
This research was motivated by the low level of students' knowledge of Bima traditional cuisine due to the limited availability of interactive and engaging learning media. This research aims to develop the Mbojo Culinary Application in local content learning to improve students' knowledge of Bima traditional cuisine is to produce a learning medium that is valid, effective, and practical in supporting the learning process of elementary school students.This research used the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, eval_uation) and a mixed methods approach. Validation was conducted by subject matter experts and media experts, while limited trials involved students in Bima Regency. The trial design was carried out in two stages, namely a small-scale trial involving 2 students as an initial representation to test the functionality of the application, and a large-scale trial involving 8 students to assess the overall feasibility of the application.The results of this study indicate that the average percentage of application feasibility based on the assessments from both validators was 87.50%, which falls under the "highly feasible" category. The Mbojo Culinary Application was also effective in improving students' knowledge of Bima traditional cuisine, with an average N-Gain score of 0.6, categorized as moderate. These results indicate that the Mbojo Culinary application can become an alternative interactive learning medium that is feasible for use and capable of supporting the preservation of Bima local culture